FAKTOR PERAN SYAHBANDAR DALAM MELAKSANAKAN PENGAWASAN, PEMERIKSAAN DAN PEMBERIAN SURAT PERSETUJUAN BERLAYAR TERHADAP KESELAMATAN PELAYARAN - Siwi, Galih Raga; Sulistyowati, Sulistyowati; Minarto, Dian; Mulatsih, Retno (STIE PENA, 2024)
Sea transportation is one of these modes of transportation, in addition to having a role as a means of transportation nationally, it can reach all regions through waters so that it can support, encourage and drive the growth of regions that have great natural resource potential in an effort to improve and distribute development and its results. In accordance with the function of the harbormaster's duty to supervise the seaworthiness of the ship which includes safety, se curity and security at the port. In this case, the port plays an important role in the port system, both in shipping, law enforcement and in all port activities. The purpose of this study was to analyze the effect of the independent variables, namely supervision, inspection, and the granting of a Sailing Approval Letter, for the dependent variable of shipping safety. The population in this study were all crew members and employees of the ships docked in May at the port of Padangbai and the sample in this study was 100 respondents with the technique used was a non-probability sampling technique, namely by using quota sampling, Kouta sampling was a technique to determine the sample. from a population that has certain characteristics to the desired number (quota). The analytical method used is descriptive analysis and quantitative analysis, the data were analyzed using multiple linear regression analysis with the help of (Software) Statistical Package For Social Science (SPSS). The results of the research by testing the hypothesis indicate that the variables of Supervision, Inspection, and Granting of Sailing Approval Letters are positive and significant for Shipping Safety in the Class IV Port Authority and Harbormaster Office Area Padangbai Port. Based on the results of the study, it can be seen that the research model of the multiple linear regression equation is Y=2,898+0,436X1+0,214X2+0,189X3+ µ. From the regression results, it can be seen that the most dominant variable affecting shipping safety is the supervision variable with a regression coefficient of 0.436. With the r square test of 0.526 or 52.6% which means that the increase in shipping safety in the KSOP class IV Padangbai area is influenced by supervision, inspection and granting of approval letters which is 52.6% and other factors that affect the improvement of shipping safety in the areas served by KSOP Class IV Padangbai by 47.4%.